A case with a large intracoronary mobile mass diagnosed with a calcified thrombus using optical frequency domain imaging and intravascular ultrasound. (28th July 2017) - Kuno, Toshiki; Hashimoto, Kenji; Imaeda, Syohei; Ryuzaki, Toshinobu; Saito, Tetsuya; Yamazaki, Hiroyuki; Tabei, Ryota; Kodaira, Masaki; Numasawa, Yohei
Objectives: A calcified thrombus is rare, but needs to be recognized and to be differentiated from calcified nodule. Methods: We report a case of acute coronary syndrome and a large intracoronary mobile mass, which was identified as a calcified thrombus by optical frequency domain imaging and intravascular ultrasound. Results: Successful direct stenting indicated that mobile mass was a calcified thrombus, not a calcified nodule. Conclusions: Cardiologists should be aware that an intracoronary mobile mass could be a calcified thrombus. This diagnosis can be confirmed through the combined use of optical frequency domain imaging and intravascular ultrasound.